Breeding Potentials of Bambara Groundnut for Food and Nutrition Security in the Face of Climate Change - Olanrewaju, Oluwaseyi Samuel; Oyatomi, Olaniyi; Babalola, Olubukola Oluranti; Abberton, Michael (Frontiers in Plant Science, 2022)
Constant production of quality food should be a norm in any community, but climate change, increasing population, and unavailability of land for farming affect food production. As a result, food scarcity is affecting some communities, especially in the developing world. Finding a stable solution to this problem is a major cause of concern for researchers. Synergistic application of molecular marker techniques with next generation sequencing (NGS) technologies can unlock the potentials hidden in most crop genomes for improving yield and food availability. Most crops such as Bambara groundnut (BGN), Winged bean, and African yam bean are underutilized. These underutilized crops can compete with the major crops such as cowpea, soybean, maize, and rice, in areas of nutrition, ability to withstand drought stress, economic importance, and food production. One of these underutilized crops, Bambara groundnut (Vigna subterranea (L.), Verdc.), is an indigenous African legume and can survive in tropical climates and marginal soils. In this review, we focus on the roles of BGN and the opportunities it possesses in tackling food insecurity and its benefits to local farmers. We will discuss BGN’s potential impact on global food production and how the advances in NGS technologies can enhance its production.